Anemia is associated with the progression of white matter disease in older adults with high blood pressure: the cardiovascular health study. - Inzitari, Marco; Studenski, Stephanie; Rosano, Caterina; Zakai, Neil A; Longstreth, William T; Cushman, Mary; Newman, Anne B (J Am Geriatr Soc, 2008)
OBJECTIVES: To investigate whether anemia predicts worsening white matter hyperintensities (WMHs) in older community-dwellers. DESIGN: Prospective cohort study. SETTING: Older community-dwellers. PARTICIPANTS: One thousand eight hundred forty-six Cardiovascular Health Study (CHS) participants (mean age 73.7 +/- 4.4, 41% male, 15.6% African American). MEASUREMENTS: Participants had hemoglobin measured and brain magnetic resonance imaging (MRI) in 1992/93 and a second brain MRI in 1997/98. Anemia was defined according to World Health Organization criteria (hemoglobin <12 g/dL in women and <13 g/dL in men). Worsening WMHs were determined according to standardized side-by-side readings. RESULTS: After 5 years, WMHs worsened in 517 participants (28%). Progression was not associated with anemia in the whole sample, in sex or race strata, or in other prespecified subgroups (participants with renal dysfunction or diabetes mellitus), except in participants with high blood pressure (>or=140/90 mmHg). Of the 678 participants with high blood pressure, those with anemia (10.5%) had a 1.79 times greater risk of WMHs worsening (95% confidence interval=1.06-2.98; P for interaction between anemia and high blood pressure=.01) independent of demographics, baseline WMHs, cardiovascular risk factors and comorbidities, medications, renal function, inflammation, and incident stroke (logistic regression models). There was no greater risk in participants with anemia with normal blood pressure. CONCLUSION: Anemia may contribute to worsening of WMHs in older adults with high blood pressure.
Keywords: Aged; Anemia; Brain; Cardiovascular Diseases; Disease Progression; Female; Humans; Hypertension; Leukoaraiosis; Magnetic Resonance Imaging; Male

Coronary artery calcium and physical function in older adults: the Cardiovascular Health Study. - Inzitari, Marco; Naydeck, Barbara L; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2008)
BACKGROUND: In older adults without clinical cardiovascular disease, coronary artery calcium (CAC) is associated with other subclinical vascular diseases, which, in turn, predict physical dysfunction. However, the association between CAC and physical function is unstudied. METHODS: In 387 older community-dwellers from the Cardiovascular Health Study without clinical cardiovascular diseases (mean age +/- standard deviation = 78.7 +/- 3.7, 35% men, 22% African Americans), CAC was measured using electron beam tomography, and physical performance was assessed by usual pace gait speed, chair stand, and tandem stand. Differences in physical performance across CAC quartiles were investigated in the whole cohort and by gender. Associations with gait speed (m/s) were assessed in multivariable models using both the continuous form of CAC score (log(CAC)) and quartiles of CAC, adjusting for demographics and comorbidities. RESULTS: No differences in physical performance were observed across CAC quartiles in the whole group. In gender-stratified analyses, a significant association was shown among women, who had progressively lower gait speed across CAC quartiles: Those with CAC > 220 walked more than 0.1 m/s slower than those with CAC < 35 (age-adjusted ptrend =.017). After multivariable adjustment, the association remained statistically significant for women in both linear (log(CAC) and gait speed, p =.025) and logistic models: Each of the top three CAC quartiles (35-220, 221-659, and > or = 660) had a more than twofold odds of walking slower than 1 m/s, compared to the lowest CAC quartile (< 35; p =.021). CONCLUSIONS: In this sample of older community-dwellers without overt cardiovascular disease, CAC was inversely related to gait speed in women, but not in men.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Calcinosis; Coronary Artery Disease; Female; Geriatric Assessment; Humans; Male; Regression Analysis; Risk Factors; Tomography, X-Ray Computed; Walking

Gait speed and survival in older adults. - Studenski, Stephanie; Perera, Subashan; Patel, Kushang; Rosano, Caterina; Faulkner, Kimberly; Inzitari, Marco; Brach, Jennifer; Chandler, Julie; Cawthon, Peggy; Connor, Elizabeth Barrett; Nevitt, Michael; Visser, Marjolein; et al. (JAMA, 2011)
CONTEXT: Survival estimates help individualize goals of care for geriatric patients, but life tables fail to account for the great variability in survival. Physical performance measures, such as gait speed, might help account for variability, allowing clinicians to make more individualized estimates. OBJECTIVE: To evaluate the relationship between gait speed and survival. DESIGN, SETTING, AND PARTICIPANTS: Pooled analysis of 9 cohort studies (collected between 1986 and 2000), using individual data from 34,485 community-dwelling older adults aged 65 years or older with baseline gait speed data, followed up for 6 to 21 years. Participants were a mean (SD) age of 73.5 (5.9) years; 59.6%, women; and 79.8%, white; and had a mean (SD) gait speed of 0.92 (0.27) m/s. MAIN OUTCOME MEASURES: Survival rates and life expectancy. RESULTS: There were 17,528 deaths; the overall 5-year survival rate was 84.8% (confidence interval [CI], 79.6%-88.8%) and 10-year survival rate was 59.7% (95% CI, 46.5%-70.6%). Gait speed was associated with survival in all studies (pooled hazard ratio per 0.1 m/s, 0.88; 95% CI, 0.87-0.90; P < .001). Survival increased across the full range of gait speeds, with significant increments per 0.1 m/s. At age 75, predicted 10-year survival across the range of gait speeds ranged from 19% to 87% in men and from 35% to 91% in women. Predicted survival based on age, sex, and gait speed was as accurate as predicted based on age, sex, use of mobility aids, and self-reported function or as age, sex, chronic conditions, smoking history, blood pressure, body mass index, and hospitalization. CONCLUSION: In this pooled analysis of individual data from 9 selected cohorts, gait speed was associated with survival in older adults.
Keywords: Aged; Cohort Studies; Female; Gait; Geriatric Assessment; Humans; Life Expectancy; Male; Survival Analysis; United States

Hypertension, white matter hyperintensities, and concurrent impairments in mobility, cognition, and mood: the Cardiovascular Health Study. - Hajjar, Ihab; Quach, Lien; Yang, Frances; Chaves, Paulo H M; Newman, Anne B; Mukamal, Kenneth; Longstreth, Will; Inzitari, Marco; Lipsitz, Lewis A (Circulation, 2011)
BACKGROUND: Our objective was to investigate the association between hypertension and concurrent impairments in mobility, cognition, and mood; the role of brain white matter hyperintensities in mediating this association; and the impact of these impairments on disability and mortality in elderly hypertensive individuals. METHODS AND RESULTS: -Blood pressure, gait speed, digit symbol substitution test, and the Center for Epidemiological Studies Depression Scale were measured yearly (1992-1999) on 4700 participants in the Cardiovascular Health Study (age: 74.7, 58% women, 17% blacks, 68% hypertension, 3600 had brain magnetic resonance imaging in 1992-1993, survival data 1992-2005). Using latent profile analysis at baseline, we found that 498 (11%) subjects had concurrent impairments and 3086 (66%) were intact on all 3 measures. Between 1992 and 1999, 651 (21%) became impaired in all 3 domains. Hypertensive individuals were more likely to be impaired at baseline (odds ratio 1.23, 95% confidence interval 1.04 to 1.42, P=0.01) and become impaired during the follow-up (hazard ratio=1.3, 95% confidence interval 1.02 to 1.66, P=0.037). A greater degree of white matter hyperintensities was associated with impairments in the 3 domains (P=0.007) and mediated the association with hypertension (P=0.19 for hypertension after adjusting for white matter hyperintensities in the model, 21% hazard ratio change). Impairments in the 3 domains increased subsequent disability with hypertension (P<0.0001). Hypertension mortality also was increased in those impaired (compared with unimpaired hypertensive individuals: HR=1.10, 95% confidence interval 1.04 to 1.17, P=0.004). CONCLUSIONS: Hypertension increases the risk of concurrent impairments in mobility, cognition, and mood, which increases disability and mortality. This association is mediated in part by microvascular brain injury.
Keywords: Aged; Aged, 80 and over; Brain; Cognition Disorders; Female; Humans; Hypertension; Kaplan-Meier Estimate; Longitudinal Studies; Magnetic Resonance Imaging; Male; Microcirculation; Mobility Limitation; Mood Disorders; Nerve Fibers, Myelinated; Retrospective Studies; Risk Factors

Subclinical vascular disease burden and risk for death and cardiovascular events in older community dwellers. - Inzitari, Marco; Arnold, Alice M; Patel, Kushang V; Mercer, Laina D; Karlamangla, Arun; Ding, Jingzhong; Psaty, Bruce M; Williamson, Jeff D; Kuller, Lewis H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Individual measures and previous composite measures of subclinical vascular disease defined high risk for cardiovascular events, but did not detect low and modest risk. A different approach might better describe the spectrum from low to high risk. Methods and Results. In the Cardiovascular Health Study, 3,252 participants without history of clinical cardiovascular disease (M ± SD 74.3 years ± 5.1, 63% women, 17% African Americans) had noninvasive vascular assessments in 1992-1993. We assigned a score of 0, 1, or 2 (no, mild, or severe abnormalities) to ankle-arm index, electrocardiogram, and common carotid intima-media thickness, based on clinical cutoffs. A summary index (range 0-6, absent to severe disease) summed individual scores. Abdominal aortic ultrasound and brain magnetic resonance imaging were collected in a subsample. Mortality and incident cardiovascular events were identified through June 2008. Event and death rates increased across index grades. Comparing grades 1 to 5+ with absent disease, and adjusting for demographics, hazard ratios for cardiovascular events within 8 years ranged from 1.1 (95% confidence interval 0.8-1.6) to 4.7 (3.4-6.9) and, for mortality, from 1.5 (1.0-2.3) to 5.0 (3.3-7.7) (p for trend across grades <.001 for both outcomes). Adjustment for cardiovascular risk factors did not substantially change the associations. The index improved mortality risk classification over demographics and risk factors in participants who did not die during the follow-up. Including in the index the aortic ultrasound and the brain magnetic resonance imaging further improved risk classification. CONCLUSIONS: Older adults with minimal subclinical vascular disease had low cardiovascular events risk and mortality. This approach might more fully account for vascular burden.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cost of Illness; Female; Humans; Male; Risk; Vascular Diseases

Subclinical vascular disease burden and longer survival. - Odden, Michelle C; Yee, Laura M; Arnold, Alice M; Sanders, Jason L; Hirsch, Calvin; DeFilippi, Christopher; Kizer, Jorge R; Inzitari, Marco; Newman, Anne B (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine the contribution of gradations of subclinical vascular disease (SVD) to the likelihood of longer survival and to determine what allows some individuals with SVD to live longer. DESIGN: Cohort study. SETTING: Cardiovascular Health Study. PARTICIPANTS: Individuals born between June 30, 1918, and June 30, 1921 (N = 2,082; aged 70-75 at baseline (1992-93)). MEASUREMENTS: A SVD index was scored as 0 for no abnormalities, 1 for mild abnormalities, and 2 for severe abnormalities on ankle-arm index, electrocardiogram, and common carotid intima-media thickness measured at baseline. Survival groups were categorized as 80 and younger, 81 to 84, 85 to 89, and 90 and older. RESULTS: A 1-point lower SVD score was associated with 1.22 greater odds (95% confidence interval = 1.14-1.31) of longer survival, independent of potential confounders. This association was unchanged after adjustment for intermediate incident cardiovascular events. There was suggestion of an interaction between kidney function, smoking, and C-reactive protein and SVD; the association between SVD and longer survival appeared to be modestly greater in persons with poor kidney function, inflammation, or a history of smoking. CONCLUSION: A lower burden of SVD is associated with longer survival, independent of intermediate cardiovascular events. Abstinence from smoking, better kidney function, and lower inflammation may attenuate the effects of higher SVD and promote longer survival.
Keywords: Aged; Aged, 80 and over; C-Reactive Protein; Carotid Intima-Media Thickness; Cohort Studies; Cystatin C; Depression; Diabetes Mellitus; Electrocardiography; Female; Humans; Inflammation; Kidney Diseases; Male; Smoking; Survival Analysis; United States; Vascular Diseases

Digit Symbol Substitution test and future clinical and subclinical disorders of cognition, mobility and mood in older adults. - Rosano, Caterina; Perera, Subashan; Inzitari, Marco; Newman, Anne B; Longstreth, William T; Studenski, Stephanie (Age Ageing, 2016)
OBJECTIVE: to examine whether psychomotor speed predicts individual and combined disorders in cognition, mobility and mood and if white matter hyperintensities explain these associations. DESIGN AND SETTING: longitudinal; Cardiovascular Health Study. SUBJECTS: 5,888 participants (57.6% women, 15.7% black, 75.1 (5.5), mean years (SD)). METHODS: psychomotor speed (Digit Symbol Substitution Test (DSST)) and small vessel disease (white matter hyperintensities (WMH)) were measured in 1992-94. Global cognition (Modified Mini-Mental State (3MS) examination), mobility (gait speed (GS)) and mood (Center for Epidemiologic Studies Depression (CES-D) scale) were measured annually over 5 years and classified as clinical, subclinical or no disorders based on established values (3MS: 80 and 85 points; GS: 0.6 and 1.0 m/s; CES-D: 10 and 5 points). Analyses were adjusted for demographics, baseline status, education, diabetes, hypertension, ankle-arm index. RESULTS: among those with no disorder in cognition, mobility and mood (N = 619) in 1992-94, being in the lowest DSST quartile compared to the highest was associated with nearly twice the odds of developing 1+ clinical or subclinical disorders (N = 413) during follow-up. Associations were stronger for incident clinical disorders in cognition (OR: 8.44, p < 0.01) or mobility (OR: 9.09, p < 0.05) than for mood (OR: 1.88, p < 0.10). Results were similar after adjustment for WMH. CONCLUSIONS: slower psychomotor speed may serve as a biomarker of risk of clinical disorders of cognition, mobility and mood. While in part attributable to vascular brain disease, other potentially modifiable contributors may be present. Further studying the causes of psychomotor slowing with ageing might provide novel insights into age-related brain disorders.